Democracy: equality and freedom as terms of debate in the post social outbreak of Chile - Vera Álvarez, Marcelo (2020)
The current state of liberal democracies turns the return to normative models of democracy and the analysis of its constituent concepts into an attractive phenomenon for political science. The wave of protests that began in Chile on October 18, 2019 has reactivated the state-market cleavage in the distribution of goods and services. Alongside this, it has rekindled the classic discussion, within political philosophy, between liberty and equality. If the social movement in Chile is equalitarian in character, a group of its opponents criticizes this ideal accusing it of being inmoral and authoritarian. Under their conception of liberty, equality necessarily implies a reduction of it. This article aims to call into question such stance through a critic of the concept of a pure negative liberty and its theorical limitations. It notes that the anti-equalitarian critic is based on conceptions of liberty and equality that ignore the ample family of principles and approaches that address this thematic, reducing it to an oversimplification. By doing so, this article aims to promote a public discussion about liberty and equality as compatible ideals for a full democracy and, especially, for Chile’s case.